Global youth perspectives on digital health promotion: a scoping review - Agata Ferretti; Shannon Hubbs; Effy Vayena (BMC Digital Health, 2023)
Abstract Background As digital technology presents the potential to enhance the accessibility and effectiveness of health promotion campaigns, adolescents and young adults are an important target population. Young people are establishing behaviors that will contribute to the quality of their health later in life, and thus understanding their particular perspectives and receptivity to digital technologies for health promotion is crucial. With this review we aimed to synthesize the published literature reporting perspectives on digital health promotion (DHP) from adolescents and young adults worldwide. Methods We conducted a scoping review of the literature on five research databases. We included papers which defined a target population of young people, and encompassed qualitative, quantitative, and mixed methods studies. Two independent reviewers thematically analyzed the included publications and provided both a quantitative and a narrative synthesis of the views of youth (namely opportunities and concerns) on digital health promotion. Results We retrieved and analyzed 50 studies which met our inclusion and exclusion criteria. The large majority of these studies were conducted in high-income countries, while only a few collected the perspectives of youth in low- or middle-income countries. Findings revealed the importance of certain technology features, such as user interface design, as well as the significance of lack of personalization or user experience friction, for example, as deterrents to engagement with DHP tools. Ethically relevant aspects, such as those related to privacy or scientific reliability of the tools, did not receive much attention from youth. Yet, DHP for particularly sensitive areas of health elicited more frequent concerns about data security and evidence of effectiveness. Conclusions Young people express distinct opinions and preferences concerning the use of digital technologies for health promotion. Our review identified a general appreciation and receptivity on the part of adolescents and young adults towards these technologies, even when taking potential risks into account.